1997
DOI: 10.2337/diab.46.7.1198
|View full text |Cite
|
Sign up to set email alerts
|

Early, but Not Advanced, Glomerulopathy Is Reversed by Pancreatic Islet Transplants in Experimental Diabetic Rats: Correlation With Glomerular Extracellular Matrix mRNA Levels

Abstract: In this study, we investigated 1) whether long-term restoration of euglycemia by means of pancreatic islet transplants is capable of preventing and/or reversing renal functional and structural alterations in an experimental model of insulin-deficient diabetes, and 2) whether changes in extracellular matrix (ECM) and cell turnover at the glomerular level and biochemical abnormalities associated with hyperglycemia correlate with the renal outcome after transplantation. Male Lewis rats, rendered diabetic by intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Since glomeruli only account for a small percentage of whole kidney cortex (29), their content of these matrix proteins was verified by immunohistochemistry, which showed higher glomerular levels of both fibronectin (Fig. 4A-D) and collagen IV (Fig.…”
Section: Fig 3 A: Representative Immunohistochemistry For Active Camentioning
confidence: 97%
“…Since glomeruli only account for a small percentage of whole kidney cortex (29), their content of these matrix proteins was verified by immunohistochemistry, which showed higher glomerular levels of both fibronectin (Fig. 4A-D) and collagen IV (Fig.…”
Section: Fig 3 A: Representative Immunohistochemistry For Active Camentioning
confidence: 97%
“…This is at variance with glomerular cell proliferation, which was not significantly affected in this experimental animal model of diabetes [7,30]. Topographical localisation and double immunohistochemistry also indicated that podocytes are the predominant apoptosing cells under these conditions, although endothelial and mesangial cells are also lost.…”
Section: Discussionmentioning
confidence: 79%
“…; Sigma Chemical, St Louis, MO, USA) [29]. Insulin-treated diabetic rats and rats showing spontaneous reversal of diabetes [30] served as control for streptozotocin effect. Rats were studied for 7 days and for 2, 4 and 6 months after initiation of the study (n=6 for both groups at each time point).…”
Section: Methodsmentioning
confidence: 99%
“…Adult (aged 8-10 weeks) male Sprague-Dawley rats (Harlan Nossan, Milan, Italy) were divided into nondiabetic (n = 22) and diabetic (n = 22) groups. Rats were made diabetic by a single injection (via the caudal vein) of streptozotocin at a dose of 60 mg/kg body wt in citrate buffer (pH 4.5) (20). The animals were housed and cared in keeping with European Community regulations, and they received water and food ad libitum.…”
Section: Experimental Designmentioning
confidence: 99%